2011
DOI: 10.3109/08039488.2011.565800
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic stability over 2 years in patients with acute and transient psychotic disorders

Abstract: A sizeable proportion of the patients with initial diagnosis of ATPD is likely to represent early manifestations of schizophrenia-related disorders. In agreement with some previous observations, our study indicates a lack of strong rationale for separating ATPD from other psychotic disorders within the ICD-10 F2 category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 14 publications
9
52
0
1
Order By: Relevance
“…These findings enhance the understanding of ATPDs and support the view that they show variations not only in incidence rates and age of onset, but also in course and outcome. It would appear that APPD is more common in females and occurs later than the subtypes with schizophrenic symptoms, which are characterized by a male preponderance, an increased risk of schizophrenia in family members, and a tendency to convert into schizophrenia and related disorders [8,9,10,11,12,13,16]. Although the predictive validity is relatively low, APPD fared better than any specific ATPD subtype in terms of both temporal stability and cases with a single episode of psychosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings enhance the understanding of ATPDs and support the view that they show variations not only in incidence rates and age of onset, but also in course and outcome. It would appear that APPD is more common in females and occurs later than the subtypes with schizophrenic symptoms, which are characterized by a male preponderance, an increased risk of schizophrenia in family members, and a tendency to convert into schizophrenia and related disorders [8,9,10,11,12,13,16]. Although the predictive validity is relatively low, APPD fared better than any specific ATPD subtype in terms of both temporal stability and cases with a single episode of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that patients with APPD are more likely to experience transition to mood disorders than those with schizophrenic or predominantly delusional symptoms. Follow-up studies reported a more favorable course and outcome of ATPDs than schizophrenia and a closer kinship to bipolar disorder [8,9,10,13,17,18,19]. However, genetic epidemiological surveys have challenged a sharp demarcation between ATPDs and schizophrenia, while the relationship to affective disorders remains less clear [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Varying transition rates have been reported in ATPDs either to schizophrenia and related disorders or affective disorders (Aadamsoo, Saluveer, Küünarpuu, Vasar, & Maron, 2011;Castagnini et al, 2013b;Jørgensen, Bennedsen, Christensen, & Hyllested, 1997;Pillmann & Marneros, 2005;Queirazza, Semple, & Lawrie, 2014;Rusaka & Rancāns, 2014;Singh, Burns, Amin, Jones, & Harrison, 2004). While younger age at onset, male gender and longer hospital admission are features more likely to be associated with increased risk of subsequent diagnosis change to schizophrenia (Aadamsoo et al, 2011;Castagnini et al, 2013b;Queirazza et al, 2014;Rusaka & Rancāns, 2014), the effect of acute onset and early remission on diagnostic stability and/or favourable outcome remains unclear.…”
Section: Introductionmentioning
confidence: 99%